Tourism, Economic Development, and Regional Inequality in Portugal: A Data-Driven Approach from 2012 to 2022 - Maria do Rosário Mira; Andreia Antunes Moura; Vânia Costa; Raquel Pereira (Tourism and Hospitality, 2025)
This study explores the regional disparities in the tourism sector in Portugal between 2012 and 2022 with the aim of understanding how the spatial distribution, typology, and scale of tourism enterprises relate to regional wage dynamics. Using a quantitative approach, the analysis draws on secondary data from the Ministry of Labour and the Bank of Portugal, incorporating information on business characteristics and average employee remuneration across NUT II or regions. A combination of descriptive statistics, linear mixed-effects regression models, time series analysis, and ANOVA tests were employed to capture both temporal and territorial variations. The findings reveal a notable concentration of larger tourism enterprises in Lisbon, the North, and the Algarve, coupled with persistent wage disparities that tend to favour these same regions. Although average wages have increased, they remain insufficient in areas with high living costs, raising concerns about tourism’s redistributive potential. The study provides empirical evidence that tourism may exacerbate rather than reduce regional inequalities. By highlighting the territorial dimension of economic outcomes, this research offers valuable insights for policymakers and contributes to a more nuanced theoretical understanding of tourism-led development.